Direct evidence for the co-manufacturing of early iron and copper-alloy artifacts in the Caucasus. (November 2020) - Erb-Satullo, Nathaniel L.; Jachvliani, Dimitri; Kakhiani, Kakha; Newman, Richard
Abstract: Models for iron innovation in Eurasia are predicated on understanding the relationship between the bronze and iron industries. In eastern Anatolia, the South Caucasus, and Iran, the absence of scientific analyses of metallurgical debris has obscured the relative chronology, spatial organization, and economic context of early iron and contemporary copper-alloy industries. Survey and excavation at Mtsvane Gora, a fortified hilltop site close to major polymetallic ore sources in the Lesser Caucasus range, recovered metallurgical debris dating to the 8th-6th centuries BC. Optical microscopy, scanning electron microscopy, and energy and wavelength dispersive spectrometry revealed evidence for both iron and copper-alloy metallurgy, including smithing and alloying. Metal particles trapped within clear iron smithing slags were contaminated with copper, arsenic, and tin, suggesting that iron and copper-alloy working took place in the same hearths. The discovery of a small fragment of unprocessed material consisting of pyrite and jarosite, minerals typical of major nearby polymetallic ore deposits, links the secondary smithing and alloying at Mtsvane Gora with nearby mining activities, though the nature of those connections remains unclear. While the earliest iron in the region probably predates the Mtsvane Gora assemblage, the remains date to a period when iron use was still expanding, and they are at present the earliest analytically confirmed, radiocarbon-dated iron metallurgical debris in the Caucasus. The remains are therefore significant for understanding the spread of iron innovation eastward from Anatolia and the Levant. When considered in light of evidence from other Near Eastern sites, the results support a model for innovation in which early iron manufacturing was at least partially integrated with the copper-alloy metallurgical economy. Highlights: Direct evidence of iron production is rare in SW Asia, especially beyond the Levant. Metallurgical debris found in 8th-6th c. BC deposits on a hilltop fortress. Aside from Fe, metallic particles in iron smithing slags contained Cu, As, and Sn. Analyses suggest iron and copper-alloy working in the same hearths. Results have implications for iron innovation and integration of metal economies.